Drawings as tools to (re)imagine space in interdisciplinary global health research - Dens, Stefanie; Nieto-Sanchez, Claudia; De Los Santos, Mario; Hawer, Thomas; Haile, Asgedom; Solari, Karla; Cisneros, Jesus; Vega, Victor; Solomon, Kalkidan; Addissie, Adamu; Yewhalaw, Delenasaw; Otero, Larissa; et al. (Frontiers in Public Health, 2022)
Understanding the role of space in infectious diseases’ dynamics in urban contexts is key to developing effective mitigation strategies. Urbanism, a discipline that both studies and acts upon the city, commonly uses drawings to analyze spatial patterns and their variables. This paper revisits drawings as analytical and integrative tools for interdisciplinary research. We introduce the use of drawings in two interdisciplinary projects conducted in the field of global public health: first, a study about the heterogeneous burden of tuberculosis and COVID-19 in Lima, Peru, and second, a study about urban malaria in Jimma, Ethiopia. In both cases, drawings such as maps, plans, and sections were used to analyze spatial factors present in the urban context at different scales: from the scale of the territory, the city, and the district, to the neighborhood and the household. We discuss the methodological approaches taken in both cases, considering the nature of the diseases being investigated as well as the natural and social context in which the studies took place. We contend that the use of drawings helps to re-imagine space in public health research by adding a multidimensional perspective to spatial variables and contexts. The processes and products of drawing can help to (a) identify systemic relations within the spatial context, (b) facilitate integration of quantitative and qualitative data, and (c) guide the formulation of policy recommendations, informing public and urban health planning.